2022
DOI: 10.3390/jpm12050802
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Ocular Surface Disease by Lateral Tarsoconjunctival Flap in Thyroid-Associated Orbitopathy Patients with Lid Retraction

Abstract: There is a high incidence of ocular surface disease (OSD) in thyroid-associated orbitopathy (TAO) patients as a result of incomplete eyelid closure and chronic inflammatory eyelid status. This study was performed to evaluate the efficacy of a lateral tarsoconjunctival flap (LTF) in improving OSD in TAO patients from the perspective of correcting eyelid closures. As a study design, TAO patients were enrolled in this study to evaluate OSD perioperatively before they were scheduled for LTF surgery. Additional lid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This resulted in objective improvements in fluorescein staining from 2+ to trace after 3 weeks of wear as well as subjective increases in comfort. Hsu et al., performed lateral tarsoconjunctival flaps in 42 patients and showed statistically significant improvements in OSDI, TBUT, Schirmer’s test, corneal and conjunctival staining scores, and meibomian gland drop out (all p<.01) 3 months postoperatively ( 19 ). Additionally, the tear osmolarity and inflammatory markers in the tear fluid (IL-6, IL-8, IL-18 and MCP-1) were significantly improved after the lateral tarsoconjunctival flaps.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This resulted in objective improvements in fluorescein staining from 2+ to trace after 3 weeks of wear as well as subjective increases in comfort. Hsu et al., performed lateral tarsoconjunctival flaps in 42 patients and showed statistically significant improvements in OSDI, TBUT, Schirmer’s test, corneal and conjunctival staining scores, and meibomian gland drop out (all p<.01) 3 months postoperatively ( 19 ). Additionally, the tear osmolarity and inflammatory markers in the tear fluid (IL-6, IL-8, IL-18 and MCP-1) were significantly improved after the lateral tarsoconjunctival flaps.…”
Section: Resultsmentioning
confidence: 99%
“…This review found lateral tarsoconjunctival flap surgery to improve dry eye parameters and decrease inflammatory markers in the tear film, but this surgical option should be reserved for patients suffering from refractory dry eye in thyroid eye disease ( 19 ). Less invasive measures focusing on tear film optimization and decreased inflammation should be trialed first, especially in patients with mild to moderate disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in order to decrease those symptoms, pharmacotherapy (anti-inflammatory eye drops, CsA eye drops, botulinum toxin injection, etc.) [ 16 20 ] or surgical intervention such as orbital decompression, correction of upper eyelid retraction, or lateral tarsoconjunctival flap surgery [ 21 23 ] should be implemented as soon as possible.…”
Section: Discussionmentioning
confidence: 99%